Results of the surgical treatment of cardiospasm - Rubio, Roberto; F. Berhouet, Luis (Cirugía del Uruguay, 1971)
An account is given of results obtained in the surgical treatment of 7 patients with cardiospasm. The operation performed was esophagogastric extramucous myotomy using a thoracic approach. In this series morbility and death rates were nil. Long-term results were excellent in 6 cases. The last case operated upon 5 months ago presented, after temporary improvement, a recurrency of dysphagia. Duration of disease in these patients was an average of four and a half years and almost five dilatations had been performed in each of these patients (average). Advantages and disadvantages of the treatment by means of dilatations versus surgery are discussed. Heller's operation modified is believed to be the best and safest treatment for cardiospasm, more so than dilatations. This operation should be performed at an early stage; it is considered unadvisable that it be performed only when dilatations have failed.